Grupo Escolar 13 de Maio e a educação primária na periferia de Uberlândia, MG - 1962-71 - Boas, Márcia Silva de Melo Villas (2015)
This study sought to build a historical understanding of the creation of the school Grupo Escolar 13 de Maio in Uberlândia, state of Minas Gerais. Built upon the suburbs, this school came to meet black and poor people s educational needs. As so it stands out as a subject matter useful to understand the relationship between education, society, politics, and ethnicity. The overall aim was to inquiry into this school s the history and social importance; the specific aims were to question interests underlying the construction of an elementary school on the outskirts and whose name symbolizes black population s social struggles, to analyze schooling everydayness, and to understand its pedagogical practices. As a documental and dialetical inquiry, this study relied upon methodological procedures such as bibliographic and documental research as well as interviews with former students and a former headmaster. Research sources included newspapers, record book of class attending, minutes, photographs, and interviews. The theoretical framework stemmed from Saviani (2009), Souza (2008; 1990), Nosella and Buffa (2008), Araújo (2009), and Veiga (2007), among others. Results show the school was set up both in a peripheral area populated by a majority of poor and black inhabitants that newspaper used to call a place of outcasts and in a setting marked by social tension between white people and black people at a time when black movement gained momentum in the world. In addition, results indicate school s alignment with a program of national educational expansion in which every school-aged child should be in schools. Such ideal meant to make Grupo Escolar 13 de Maio function in rented houses and limit its capacity of enrollment because of its inappropriate facilities. Once it started to operate in its own building, it offered pedagogy aimed to meet working class demands for education as a means of upward social mobility. Part of its educational practices had bonds with companies and industries that sponsored school events and were opened to educational trips to their facilities so that to make students and teachers familiar with it. Almost 50 years after its building was erected, again the school had to operate in a rented house and reduce number classes due to not-quite-clear impediments related to public administration. It s as if it d gone back to its early days.